Fracture assessment of magnetostrictive materials - M. Peron; SMJ. Razavi; F. Berto; J. Torgersen; M. Colussi (Fracture and Structural Integrity)
Giant magnetostrictive materials are gaining interest in the field of smart material, especially the commercially known Terfenol-D, that is an alloy made out of iron, terbium and dysprosium (Tb0.3Dy0.7Fe1.9). Since these smart materials are subjected to both mechanical loads and magnetic field during their industrial applications, an extensive characterization on the influence of a magnetic field and of defects on their fracture behavior is needed. Very few works can be found in literature about this topic and, thus, the purpose of this work is to partially fill this lack by means of three-point bending tests on single-edge pre-cracked Terfenol-D specimens. Failure loads have been measured at different loading rates and under magnetic fields of various intensities. Since giant magnetostrictive materials are very brittle, the strain energy density (SED) approach has been exploited by means of couplefield finite element analyses. SED has revealed itself as a robust parameters in the assessment of the magnetic field and loading rate effects on fracture resistance, allowing also to propose a relationship between the radius of the control volume and the loading-rate